The potential of misdiagnosis of high IQ youth by practicing mental health professionals: A mixed methods study. (2nd July 2020) - Bishop, James C.; Rinn, Anne N.
ABSTRACT: The difficulty of distinguishing between genuine disorder and characteristics that can be attributed to high IQ increases the likelihood of diagnostic error by mental health practitioners. This mixed methods study explores the possibility of misdiagnosis of high IQ youth by mental health professionals. Participants were private practice mental health professionals ( n = 330) who were presented with case study vignettes illustrating high IQ youth exhibiting characteristics associated with their population. Participants then completed a questionnaire and provided an assessment of the hypothetical client. Classification and Regression Tree (CART) analysis was utilized to develop a decision tree to predict the likelihood of a diagnosis of disorder being rendered for high IQ youth experiencing behavioral or emotional issues related to their intelligence. We also examined the stated rationale of the participants in arriving at their clinical judgments to determine what themes and commonalities emerged. The study found that, regardless of whether high IQ is suggested as a possible explanation of the presenting issues of a high IQ youth, mental health clinicians still leaned toward some type of diagnosis of disorder (82.9% without suggestion of high IQ vs. 78.4% with suggestion, difference 4.5%). The results of this study provide much-needed empirical exploration of the concern for misdiagnosis of high IQ youth and inform clinical practice and education.